2017
DOI: 10.1158/1078-0432.ccr-15-1169
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the EGFR/STAT3/CEBPD Axis Reverses Cisplatin Cross-resistance with Paclitaxel in the Urothelial Carcinoma of the Urinary Bladder

Abstract: Purpose: Cisplatin (CDDP) is frequently used in combination chemotherapy with paclitaxel for treating urothelial carcinoma of the urinary bladder (UCUB). CDDP cross-resistance has been suggested to develop with paclitaxel, thus hindering successful UCUB treatment. Therefore, elucidating the mechanisms underlying CDDP-induced anticancer drug resistance is imperative and may provide an insight in developing novel therapeutic strategy.Experimental Design: Loss-of-function assays were performed to elucidate the ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…Aberrant STAT3 activation has been implicated in trastuzumab resistance in HER2‐positive breast and gastric cancers . Moreover, STAT3 is involved in resistance to antimicrotubule agents, and the combination of taxane and a STAT3 inhibitor was showed to exert enhanced cytotoxicity towards STAT3‐dependent cell lines . The present study first showed that STAT3 is aberrantly activated in cells exposed to long‐term treatment with T‐DM1 and confers cells resistance.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Aberrant STAT3 activation has been implicated in trastuzumab resistance in HER2‐positive breast and gastric cancers . Moreover, STAT3 is involved in resistance to antimicrotubule agents, and the combination of taxane and a STAT3 inhibitor was showed to exert enhanced cytotoxicity towards STAT3‐dependent cell lines . The present study first showed that STAT3 is aberrantly activated in cells exposed to long‐term treatment with T‐DM1 and confers cells resistance.…”
Section: Discussionmentioning
confidence: 49%
“…36 Moreover, STAT3 is involved in resistance to antimicrotubule agents, and the combination of taxane and a STAT3 inhibitor was showed to exert enhanced cytotoxicity towards STAT3-dependent cell lines. 37,38 The present study first showed that STAT3 is aberrantly activated in cells exposed to long- Signal transducer and activator of transcription 3 (STAT3) activation was measured on western blotting. D, BT-474 and BT-474/KR cells were cultured separately, and lysates were mixed at a 1:1 ratio, or BT-474 and BT-474/KR cells were co-cultured at a 1:1 ratio.…”
Section: Stat3 Inhibition Overcomes T-dm1 Resistance In Vivomentioning
confidence: 86%
“…In urothelial carcinoma and bladder carcinoma, S3I-201 overcame resistance to paclitaxel and cisplatin (W. J. Wang, et al, 2016). Additionally, S3I-201 sensitized esophageal squamous cell carcinoma to radiation (C. Zhang, et al, 2014).…”
Section: Small Molecule Inhibitors Targeting the Sh2 Domainmentioning
confidence: 99%
“…Recent phase III clinical trials have found that a PCG (paclitaxel plus cisplatin plus gemcitabine) regimen, consisting of the addition of paclitaxel to a standard chemotherapy regimen of cisplatin plus gemcitabine (GC), can improve the overall response rate and overall survival rate of patients with BUC (7). However, acquired or de novo resistance to paclitaxel limits its clinical application in the treatment of BUC, and the identification of approaches to sensitize BUC to paclitaxel remains a significant clinical challenge (8,9).…”
Section: Introductionmentioning
confidence: 99%